1977
DOI: 10.1021/jm00212a022
|View full text |Cite
|
Sign up to set email alerts
|

Lipophilicity and serotonin agonist activity in a series of 4-substituted mescaline analogs

Abstract: Replacement of the 4-methoxy of mescaline with higher alkyl homologues or with bromine led to increased activity at serotonin receptors in a sheep umbilical artery preparation. This activity appears correlated with lipophilicity, as measured by 1-octanol-water partition coefficients, but drops off when the 4-substituent is about five atoms in length. It is suggested that 3,4,5-trisubhe 2,4,5-substitution pattern.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

1977
1977
2019
2019

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 0 publications
1
13
0
Order By: Relevance
“…66 This importance also is evident in 3,4,5-substituted mescaline analogs bearing more hydrophobic substituents in the 4-position. 67 A later study identified a steric limitation to the size of the 4-substituent, suggesting that an alkyl group of only about three carbon atoms was tolerated before the activity dropped off. 68 By contrast, polar 4-substituents such as OH, NH 2 , and COOH gave compounds with very low affinity (K i > 25,000 nM).…”
Section: Ring Substituentsmentioning
confidence: 99%
“…66 This importance also is evident in 3,4,5-substituted mescaline analogs bearing more hydrophobic substituents in the 4-position. 67 A later study identified a steric limitation to the size of the 4-substituent, suggesting that an alkyl group of only about three carbon atoms was tolerated before the activity dropped off. 68 By contrast, polar 4-substituents such as OH, NH 2 , and COOH gave compounds with very low affinity (K i > 25,000 nM).…”
Section: Ring Substituentsmentioning
confidence: 99%
“…Reduction of the resulting ester 11 with diisobutylaluminum hydride (DIBAL-H) gave benzylic alcohol 12 . Although the conversion of 12 to the benzyl chloride has been reported [44], we adopted a more convenient and higher yielding approach. This involved refluxing a mixture of 12 and triphenylphosphine in dry carbon tetrachloride for two hours [35,45,46] to give 13 in 93% yield.…”
Section: Resultsmentioning
confidence: 99%
“…This involved refluxing a mixture of 12 and triphenylphosphine in dry carbon tetrachloride for two hours [35,45,46] to give 13 in 93% yield. Treatment of 13 with sodium cyanide in dimethyl sulfoxide afforded benzyl nitrile 14 in 87% yield [35,44]. Sequential deprotonation of 14 using potassium bis(trimethylsilyl)amide and cyclobisalkylation using 1,4-dibromobutane in tetrahydrofuran (THF) at 0 °C produced cyclopentyl nitrile 15 in 70% yield [35,47].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We were able to reduce the nitriles 9 to the amines 11 in high yield using cobalt boride44 without the epimerization that occurred when lithium aluminum hydride or Raney nickel were employed. Highest yields were achieved using potassium borohydride, rather than sodium borohydride, possibly due to its higher stability in methanol.…”
Section: Resultsmentioning
confidence: 99%